Randomized Phase II Study of Docetaxel plus Personalized Peptide Vaccination versus Docetaxel plus Placebo for Patients with Previously Treated Advanced Wild Type EGFR Non-Small-Cell Lung Cancer. (4th May 2016) - Takayama, Koichi; Sugawara, Shunichi; Saijo, Yasuo; Maemondo, Makoto; Sato, Atsushi; Takamori, Shinzo; Harada, Taishi; Sasada, Tetsuro; Kakuma, Tatsuyuki; Kishimoto, Junji; Yamada, Akira; Noguchi, Masanori; et al.
Abstract : Objectives . To evaluate the efficacy and safety of personalized peptide vaccination (PPV) combined with chemotherapy for patients with previously treated advanced non-small-cell lung cancer (NSCLC). Patients and Methods . Previously treated PS0-1 patients with IIIB/IV EGFR (epidermal growth factor receptor) wild genotype NSCLC were randomly assigned to docetaxel (60 mg/m 2 on Day 1) plus PPV based on preexisting host immunity or docetaxel plus placebo. Docetaxel administration was repeated every 3 weeks until disease progression. Personalized peptides or placebo was injected subcutaneously weekly in the first 8 weeks and biweekly in subsequent 16 weeks. The primary efficacy endpoint was progression-free survival (PFS). Results . PPV related toxicity was grade 2 or less skin reaction. The median PFS for placebo arm and PPV arm was 52 days and 59 days, respectively. There was no significant difference between two arms by log-rank test (p = 0.42 ). Interestingly, PFS and overall survival (OS) in humoral immunological responder were significantly longer than those in nonresponder. Conclusion . PPV did not improve the survival in combination with docetaxel for previously treated advanced NSCLC. However, PPV may be efficacious for the humoral immunological responders and a further clinical investigation is needed.